Root-flipped multiband refocusing pulses - Sharma, Anuj (Magn Reson Med, 2015)
PURPOSE: To design low peak power multiband refocusing radiofrequency (RF) pulses, with application to simultaneous multislice spin echo MRI. THEORY AND METHODS: Multiband Shinnar-Le Roux β polynomials were designed using convex optimization. A Monte Carlo algorithm was used to determine patterns of β polynomial root flips that minimized the peak power of the resulting refocusing pulses. Phase-matched multiband excitation pulses were also designed to obtain linear-phase spin echoes. Simulations compared the performance of the root-flipped pulses with time-shifted and phase-optimized pulses. Phantom and in vivo experiments at 7 T validated the function of the root-flipped pulses and compared them to time-shifted spin echo signal profiles. RESULTS: Averaged across number of slices, time-bandwidth product, and slice separation, the root-flipped pulses have 46% shorter durations than time-shifted pulses with the same peak RF amplitude. Unlike time-shifted and phase-optimized pulses, the root-flipped pulses excitation errors do not increase with decreasing band separation. Experiments showed that the root-flipped pulses excited the desired slices at the target locations, and that for equivalent slice characteristics, the shorter root-flipped pulses allowed shorter echo times, resulting in higher signal than time-shifted pulses. CONCLUSION: The proposed root-flipped multiband RF pulse design method produces low peak power pulses for simultaneous multislice spin echo MRI.